Towards an understanding of household renewable energy transitions - Daminabo Pokubo; Dennis Pepple; Amin Al-Habaibeh (Journal of Innovation & Knowledge (JIK), 2024)
Purpose With a population of over 200 million, 60% of Nigerian households rely on conventional energy resources, known to be contributors to climate change. To address these challenges, the Nigerian government is pursuing its Renewable Energy Master Plan of transitioning to renewable energy resources to mitigate household dependence on conventional energy resources and diversify the country's energy mix. However, the process transition has been met with setbacks and at a slow pace. Method Between 2018 and 2022, a country-level survey was administered to households in Nigeria, and 746 responses were collected. Findings The study indicates that energy stacking is prevalent in urban and rural households, characterised by significant consumption inertia of conventional and traditional solid biomass fuels, followed by partial substitution of firewood for liquified natural gas (LPG) and fuel-based generators for solar panels. Originality/value This study makes a valuable contribution to existing literature on household energy transition in developing countries by uncovering the spatial heterogeneity of households in their pursuit of successful energy transition. We reveal how participants' cultural preferences may influence their decision to use traditional cooking methods instead of electricity. Thus, shedding more insights into the fluidity of energy stacking behaviour in the Nigerian context. Practical implications This paper presents a novel investigation into the underlying factors of household energy transitions in Nigeria. It identifies factors influencing the transition process and household energy motives that could potentially inform and influence the Nigerian government's policy decisions on energy transition.
Keywords: K32; P18; Q42; 650; Renewable energy; Energy transitions; Energy stacking; Nigeria; Transition barriers